PRODUKSI SIMBOL DALAM SAMPUL BUKU SASTRA TERBITAN GRAMEDIA - Saeful Anwar (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
As the design and printing technology develops rapidly, the covers’ design of literary books on store develops as well. The covers tell not only title, writer’s name, and publisher, but also show textual symbols such as subtitle, phrases describing title, phrases describing writer, book category, quotes of the content, other writer’s comment, and more. Those additional texts make the cover look full. Gramedia is one of the publishers which keeps putting only title and writer’s name on the book covers without adding up more additional texts mentioned above. Instead, the publisher put the additional texts on the back cover. This article aims at explaining why Gramedia keeps the design of book covers that way. This article applies method of Bourdieu’s theory on literary sociology. The result shows that Gramedia applies a strategy of symbolic capital exchange among the writers whose works published by Gramedia. The symbolic capital exchange is used indirectly to increase the literary books’ sale. Gramedia takes a subtle way of the strategy to keep the symbolic capital of the books and their writers affiliated with the publisher. Gradually the publisher gathers more symbolic capital that consequently increase its economic capital.Keywords: symbol production, Gramedia, literary books’ covers, literary sociology, Bordieu.